Manipulation of the Buried Interface for Robust Formamidinium‐based Sn−Pb Perovskite Solar Cells with NiOx Hole‐Transport Layers. (2nd March 2023) - Zhou, Yuan; Wang, Zhen; Jin, Junjun; Zhang, Xiang; Zou, Junjie; Yao, Fang; Zhu, Zhenkun; Cui, Xiaxia; Zhang, Dan; Yu, Yanhua; Chen, Cong; Zhao, Dewei; et al.
Abstract: Low band gap tin‐lead perovskite solar cells (Sn−Pb PSCs) are expected to achieve higher efficiencies than Pb‐PSCs and regarded as key components of tandem PSCs. However, the realization of high efficiency is challenged by the instability of Sn 2+ and the imperfections at the charge transfer interfaces. Here, we demonstrate an efficient ideal band gap formamidinium (FA)‐based Sn−Pb (FAPb0.5 Sn0.5 I3 ) PSC, by manipulating the buried NiOx /perovskite interface with 4‐hydroxyphenethyl ammonium halide (OH‐PEAX, X=Cl −, Br −, or I − ) interlayer, which exhibits fascinating functions of reducing the surface defects of the NiOx hole transport layer (HTL), enhancing the perovskite film quality, and improving both the energy level matching and physical contact at the interface. The effects of different halide anions have been elaborated and a 20.53 % efficiency is obtained with OH‐PEABr, which is the highest one for FA‐based Sn−Pb PSCs using NiOx HTLs. Moreover, the device stability is also boosted. Abstract : We report a highly efficient and stable formamidinium‐based Sn−Pb (FASn0.5 Pb0.5 I3 ) perovskite solar cell with NiOx hole‐transport layer, which is realized by manipulating the buried NiOx /perovskite interface with multifunctional 4‐hydroxyphenethyl ammonium halide (OH‐PEAX, X=Cl −, Br − or I − ) interlayer.